Learning Model Development of Memorizing The Qur'an Through Integration of Internal and External Representation - Hisban Thaha; Edhy Rustan; Subhan Subhan (JETL (Journal of Education, Teaching and Learning), 2021)
This research aims to create a learning model of memorization of the Qur'an based on the nature of the brain that tends to require relevance between the projection of information that occurred internally in the brain (internal representation) and externally presented information outside the brain (external representation). Integration of the two modes of representation was carried out through a developmental study by adopting Research and Development (R & D) from Borg and Gall as a reference for the development of conceptual frameworks and memory models of Y Wang as a reference framework of the development of operational stages. From the model development process, several components of the model implementation have successfully been developed. The model implementation was operationally integrated with internal and external representation modes such as Phase I: the formulation of indicators, Phase II diagnostic assessment dealing with prior al-Qur’an memorizing ability, Phase III Conditioning students, Phase IV Coding memorizing materials, and Phase V repetition and recalling memorizing outcomes.